VIRION DNAs STRUCTURE OF TEMPERATE ERWINIOPHAGES 49 AND 59 - М. А. Златогурська; Ф. І. Товкач (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
The aim was to conduct a comparative study of the phages 49 and 59 virion DNAs. Methods. Properties of phage DNA were studied using the standard restriction and bioinformatic analyses. Results. The genomes of erwiniaphages 49 and 59 encode 84 open reading frames.57 and 52 hypothetical proteins with unknown function were identified within the genome of phage 49 and 59, respectively. The search through NCBI databases indicates that phage 49 has no viral homologs among genomes of prokaryotic viruses. In case of phage 59, it is Cronobacter sakazakii bacteriophage ENT47670. It was identified that the phages 49 and 59 share 47 % homologies of nucleotide sequences. Most of identical open reading frames belong to the structural region of the genome and the host cell lysis module. It has been shown that the genomes of both bacteriophages are permuted and packaged according to the headful mechanism. Phage 59 is characterized by circular permutation of the genome, while phage 49 has discrete permutation. The virion DNA of phage 49 has an abnormal cleavage site for SmaI restriction enzyme that, unlike the rest SmaI-sites, is not completely hydrolyzed. Conclusions. Temperate bacteriophages 49 and 59 are not identical to the other known prokaryotic viruses and belong to unique phages of Siphoviridae family.